2022
DOI: 10.3390/molecules27020547
|View full text |Cite
|
Sign up to set email alerts
|

Anti-α-Glucosidase and Antiglycation Activities of α-Mangostin and New Xanthenone Derivatives: Enzymatic Kinetics and Mechanistic Insights through In Vitro Studies

Abstract: Diabetes mellitus is characterized by chronic hyperglycemia that promotes ROS formation, causing severe oxidative stress. Furthermore, prolonged hyperglycemia leads to glycation reactions with formation of AGEs that contribute to a chronic inflammatory state. This research aims to evaluate the inhibitory activity of α-mangostin and four synthetic xanthenone derivatives against glycation and oxidative processes and on α-glucosidase, an intestinal hydrolase that catalyzes the cleavage of oligosaccharides into gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 53 publications
1
10
0
Order By: Relevance
“…To study the type of interaction between α–glucosidase and baicalein, the plot of enzyme activity ( v ) versus α–glucosidase enzyme concentration was obtained ( Figure 7 C), suggesting a concentration–dependent reversible interaction since all straight lines obtained at different concentrations of baicalein pass through the origin of the axes, and their slope decreased with increasing concentrations of the inhibitor. Previous research showed similar behavior for other natural compounds, for example, luteolin, morin, magnolol, and α–mangostin [ 48 , 50 , 51 , 52 ]. Furthermore, the type of baicalein inhibition was also estimated with Michaelis–Menten and Lineweaver–Burk plots ( Figure 8 A,B) obtained using different substrate concentrations (0.5, 1.0, 1.5 and 2.0 mM p NPG), while maintaining constant enzyme concentration (0.05 µM).…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…To study the type of interaction between α–glucosidase and baicalein, the plot of enzyme activity ( v ) versus α–glucosidase enzyme concentration was obtained ( Figure 7 C), suggesting a concentration–dependent reversible interaction since all straight lines obtained at different concentrations of baicalein pass through the origin of the axes, and their slope decreased with increasing concentrations of the inhibitor. Previous research showed similar behavior for other natural compounds, for example, luteolin, morin, magnolol, and α–mangostin [ 48 , 50 , 51 , 52 ]. Furthermore, the type of baicalein inhibition was also estimated with Michaelis–Menten and Lineweaver–Burk plots ( Figure 8 A,B) obtained using different substrate concentrations (0.5, 1.0, 1.5 and 2.0 mM p NPG), while maintaining constant enzyme concentration (0.05 µM).…”
Section: Resultsmentioning
confidence: 56%
“…The inhibitory activity of baicalein and baicalin was studied using the α–glucosidase assay, with p NPG as substrate and acarbose as positive control [ 47 , 48 ]. The absorbance curves were detected during the 60 min reaction between enzyme (0.05 µM) and p NPG (2 mM) alone and in the presence of different concentrations of baicalein (1–100 µM), revealing a concentration-dependent inhibition of enzyme activity ( Figure 7 A).…”
Section: Resultsmentioning
confidence: 99%
“…AGEs are involved in the pathogenesis of diabetes-related complications, including cardiomyopathy, retinopathy and nephropathy (64). At a 25 µM concentration, α-mangostin was found to reduce the production of AGEs (65). In another study, the treatment of mice with STZ-induced diabetes with α-mangostin resulted in decreased glycated hemoglobin levels and reduced key gluconeogenic enzymes fructose-1-6-bisphosphatase and glucose-6-phosphatase lowering glucose production (66).…”
Section: Antidiabetic Effects Of α-Mangostinmentioning
confidence: 99%
“…The mechanisms through which α-mangostin affects these enzymes remain unknown. However, a recent study investigating α-mangostin and α-glucosidase suggested, that in the presence of α-mangostin, α-glucosidase has a more α-helical secondary structure, making it more compact and decreasing its catalytic activity (65). Acting via these mechanisms, antioxidant enzymes including SOd, GPx, cAT, GSH are increased and oxidative stress markers including MdA and ROS are reduced.…”
Section: Antioxidant Effects Of α-Mangostinmentioning
confidence: 99%
“…The products formed are detected at 405 nm. The change in absorbance is related to the [39] In this work, the results were expressed as inhibition (%) versus concentration and were presented in Table 1. Acarbose was used as a positive control.…”
Section: In Vitro Biological Effects Of the Phthalocyaninesmentioning
confidence: 99%